Exploring information practices of ethnic minorities with small populations in poverty alleviation resettlement areas in China - Jing, Peng; Ming, Zhu (Information Research an international electronic journal, 2022)
Introduction: This study explored the everyday information practices of ethnic minorities with small populations in resettlement poverty alleviation areas of Yunnan, China, to determine the conditions affecting their information practices. Method: A qualitative approach was conducted, and data were collected through comprehensive interviews involving forty-eight participants. Analysis: This study applied information practices as a conceptual tool to understand these ethnic minorities’ information needs, acquisition and sharing. The data were statistically analysed and processed using three qualitative data coding analysis levels to identify the conditions that affected their everyday information practices. Results: The research findings demonstrated that with the change in living space and social communication relationship, the information practice of the minorities changed considerably. In addition, their ethnic identity, spatial conversion and social integration were the main conditions that could influence everyday information practices after moving into a new environment. Conclusion: The results promoted the understanding of ethnic characteristics as conditions that could influence everyday information practices after the spatial and social environment changes of ethnic minorities with small populations.